Cinco de Mayo - Schuh, Mari C., 1975- (Kaleidoscope Publishing, 2025)
"Get ready to have lots of fun! Cinco de Mayo is a day of music, dancing, food, and parades. Learn how people celebrate Mexican culture on this day. Read about this holiday's history, too"--
Includes index.
"Bigfoot Jr."
Grades K-1 Kaleidoscope Publishing
Ages 5 Kaleidoscope Publishing
Keywords: Cinco de Mayo (Mexican holiday) -- Juvenile literature; Puebla, Battle of, Puebla de Zaragoza, Mexico, 1862 -- Juvenile literature; Mexico -- Social life and customs -- Juvenile literature; Readers (Publications)